2020
DOI: 10.3389/fcimb.2020.00050
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology, Antibiotic Resistance, and Virulence Traits of Stenotrophomonas maltophilia Strains Associated With an Outbreak in a Mexican Tertiary Care Hospital

Abstract: Stenotrophomonas maltophilia, an emerging opportunistic pathogen, is widely distributed in the environment the resistance mechanisms, and virulence factors of this bacterium facilitate its dissemination in hospitals. This study aimed to characterize the molecular epidemiology of S. maltophilia strains associated with an outbreak in the Children's Hospital of México Federico Gómez (HIMFG). Twenty-one clinical S. maltophilia strains were recovered from cultures of blood and urine samples from 10 pediatric patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 49 publications
3
39
0
Order By: Relevance
“…In agreement with previous studies [ 15 , 16 , 17 , 18 , 33 ], our findings showed that the ability to form biofilm is highly preserved in clinical S. maltophilia isolates, albeit with significant interstrain variability. Biofilm formation was noted among both the pathogenic and non-pathogenic strains, which suggests its essential role for bacterial persistence regardless of the colonization sites.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with previous studies [ 15 , 16 , 17 , 18 , 33 ], our findings showed that the ability to form biofilm is highly preserved in clinical S. maltophilia isolates, albeit with significant interstrain variability. Biofilm formation was noted among both the pathogenic and non-pathogenic strains, which suggests its essential role for bacterial persistence regardless of the colonization sites.…”
Section: Discussionsupporting
confidence: 93%
“…The isolates from blood showed the highest capacity for biofilm formation, while those isolated from airways of CF patients produced the lowest amounts of biofilm. Our findings are consistent with an increased adherence to human bladder HTB-9 cells by blood-derived S. maltophilia strains compared to those from environmental or urinary sources [17].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…On the other hand, recent research report opined that 11% of Cystic Fibrosis (CF) patients can be infected by S. maltophilia. Thus, high incidence of infections due to S. maltophilia can be expected in immunocompromised patients [4]. Several factors such as intrinsic resistance to antimicrobial agents, production of proteolytic enzymes and other pathogenic extracellular enzymes such as DNase, RNase, elastase, lipase, hyaluronidase, mucinase and hemolysin [3].…”
Section: Introductionmentioning
confidence: 99%
“…The transmission of S. maltophilia within the hospital setting is rarely seen, and it usually occurs as a result of a cross-contamination issue [30]. Nevertheless, contained S. maltophilia outbreaks within the ICU of a hospital setting have been reported associated with contaminated bronchoscopes [12], and superficial surfaces near the patient, such as shower outlets [31], faucets [32] and drinking water supplying devices for ICU patients [33].…”
Section: Plos Onementioning
confidence: 99%